QUO VADIMUS SARTORI? POLITICAL SCIENCE AND PUBLIC POLICIES WITHIN THE FRAMEWORK OF A CONTROVERSY (Andamios, Revista de Investigación Social, 2009)
In October of 2004, Giovanni Sartori published a brief article, “Where is political science going?”, that generated a long controversy. In the notes that follow I am going to retake this dispute but moving the attention from the mainstream of political science to the studies of public policies. My purpose is to pay attention in one of the outstanding problems marked by Sartori: the weak connection between theory and practice. My main argument has two claims. On the one hand, I maintain that the critical analysis offered by professor Sartori is applied to some aspects of the studies of public policies, but not to others. On the other hand, I indicate that their critics and proposals are up to a certain point adapted, but also are little realistic, and to a certain extent they are insufficient, because he concentrates his reflection on the epistemological aspects of knowledge but he neglects the politicalinstitutional aspects largely.
Keywords: Political science; public policy; production of knowledge; decisión-making; expert knowledge